Handbook of magnetic materials. Volume 11 - Buschow, K. H. J.; ScienceDirect eBooks (Amsterdam ; Oxford : North-Holland, 1998)
Volume 11 of this prestigious series, as the preceding volumes, has a dual purpose. As a textbook it is intended to be of assistance to those who wish to be introduced to a given topic in the field of magnetism without the need to read the vast amount of literature published. As a work of reference it is intended for scientists active in magnetism research. In keeping with this dual purpose, Volume 11 of the Handbook is composed of topical review articles written by leading authorities. In each of these articles an extensive description is given in graphical as well as in tabular form, much emphasis being placed on the discussion of the experimental material in the framework of physics, chemistry and materials science. Chapter one focuses on the growing interest in intermetallic compounds based on uranium. Recent research activities have finally led to the crystallisation of new concepts in actinide magnetism which, together with the large amount of experimental work are reviewed in this chapter. The last few decades have witnessed quite an extraordinary development in magnetic recording technology. In the near future magnetic recording technology will have an enormous growth potential, one of it's main aims being the further reduction in the peripheral device sizes while maintaining an increase in capacity. Chapter two deals with the magnetism and materials aspects of hard disk media which are the most prominent type of mass storage today, due to their low cost, high speed and relatively high storage capacity. Magnets based on rare earth elements are unequalled with regard to coercivity and maximum energy production. Considerable progress has been made in the development of rare earth based permanent magnets which goes hand in hand with a better understanding of the physical properties and especially the magnetism of the underlying class of materials. Chapter three presents a survey of the physical principles involved with this technique and how these can be applied advantageously to the study of strongly ferromagnetic materials. The final chapter is devoted to inelastic neutron scattering when applied to study the crystal field interaction in lanthanide compounds. Included in this review is a description of how this technique is complementary to various other modern and conventional techniques.
Includes indexes.
Print version record.
Elsevier
Keywords: Magnetic materials; Magnetism; Magnetic materials; Magnetism; Ferromagnetismo; Materiais magnéticos.; Electronic books